Macroeconomic Policy Making and Current Account Imbalances in the Euro Area - Taiki Murai; Gunther Schnabl (Credit and Capital Markets – Kredit und Kapital, 2021)
The paper analyses the role of fiscal and monetary policy for the development of the current account imbalances in the euro area, including the most recent developments during the coronavirus crisis. Several financial transmission channels such as international bank lending, changes in TARGET2 balances, international rescue credit and government bond purchases of euro area central banks are identified. It is found that differing fiscal policy stances which have interacted differently with the ECB's monetary policy have been at roots of first diverging and then converging current account positions in the euro area. Since the European financial and debt crisis, public financing mechanisms and the unconventional monetary of the ECB have contributed to the persistence of intra-euro area current account imbalances.
Keywords: F33; F42; H62; F32; 330; Current account; current account imbalances; financial account; euro; EU; European Monetary Union; monetary policy; fiscal policy; TARGET2